2007
DOI: 10.1523/jneurosci.4844-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Cortical Plasticity in Learning to Discriminate Modulation Rate

Abstract: The discrimination of temporal information in acoustic inputs is a crucial aspect of auditory perception, yet very few studies have focused on auditory perceptual learning of timing properties and associated plasticity in adult auditory cortex. Here, we trained participants on a temporal discrimination task. The main task used a base stimulus (four tones separated by intervals of 200 ms) that had to be distinguished from a target stimulus (four tones with intervals down to ϳ180 ms). We show that participants' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 49 publications
5
64
0
Order By: Relevance
“…Other studies demonstrated growing evidence that the adult auditory cortex is a dynamic and adaptive processing center. This has been shown in auditory perceptual learning studies, in which long-lasting neuronal changes were observed in the auditory cortex of animals [45,46] and human beings [47,48] after intensive auditory training.…”
Section: Advances In Clinical Audiologymentioning
confidence: 52%
See 1 more Smart Citation
“…Other studies demonstrated growing evidence that the adult auditory cortex is a dynamic and adaptive processing center. This has been shown in auditory perceptual learning studies, in which long-lasting neuronal changes were observed in the auditory cortex of animals [45,46] and human beings [47,48] after intensive auditory training.…”
Section: Advances In Clinical Audiologymentioning
confidence: 52%
“…Furthermore, postraining results were not statistically signiicant, possibly due to the short duration. Data in the literature suggest the need for more robust training that can guarantee beter learning on the test, in order to be able to observe diferences [34,[45][46][47][48].…”
Section: Personal Experience Regarding the Present Studymentioning
confidence: 99%
“…Data from humans indicate no perceptual generalization and knowledge transfer across sounds from different perceptual classes and, therefore, no performance benefit in discrimination when switching the sounds between the classes in a discrimination task (3,5,20,27). This interpretation explains why we did not see a beneficial effect when switching from the easy PT to the hard AM discrimination task (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…1A). Because the stimulus classes in the two tasks were different, human studies suggest that the benefit (hard-to-easy effect) was not based on knowledge of or generalization across stimuli (3,5,20,27) but rather was based on implicitly learned information integration (30,31). Integration of information about the stimuli, the procedural context, and the acquired cognitive skills in the shuttle-box seems to be the key for understanding the curves of discrimination performance of our mice in Fig.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation